Multi-Center Validation Study of Automated Classification of Pathological Slowing in Adult Scalp Electroencephalograms Via Frequency Features - Peh, Wei Yan (WORLD SCIENTIFIC PUBL CO PTE LTD, 2021)
10.1142/S0129065721500167